Pengaruh Literasi, Inklusif Keuangan Syariah dan Locus Of Control Terhadap Kinerja Keuangan dalam Meningkatkan Usaha Mikro Kecil dan Menengah (UMKM) di Kota Bandar Lampung - Krismadayanti, Krismadayanti; Noviarita, Heni; Iqbal, Muhammad (ITB AAS INDONESIA Surakarta, 2023)
There can be no doubt about the role of UMKM in developing the Indonesian economy. The potential of UMKM is an opportunity to develop markets and industry in Indonesia, especially in the real sector. However, in reality, opportunities for UMKM to develop are often experienced by the business actors themselves. This research aims to analyze whether there is an influence of Financial Literacy, Locus of Control Sharia Financial Inclusion on improving the financial performance of UMKM in Bandar Lampung City. The type of data used is primary data obtained from questionnaires or questionnaires of UMKM players in the city of Bandar Lampung which were analyzed using multiple linear regression with the help of the SPSS 21 program. The results of this research simultaneously show that financial literacy increases financial performance with a significance of 0.984, so more greater than 0.05 (0.984 > 0.05) so that the research data is normally distributed. Meanwhile, the partial test shows that financial literacy does not have an impact on improving the financial performance of MSMEs in Bandar Lampung City. Meanwhile, partially Sharia Financial Inclusion and Locus of Control have an effect on improving the financial performance of UMKM in Bandar Lampung City. The Adjusted coefficient of determination is 0.43.6 or 43.6%.